STRUCTURAL RELIABILITY OF THE NIGERIAN GROWN ABURA TIMBER BRIDGE BEAM SUBJECTED TO BENDING AND DEFLECTION FORCES (Nigerian Journal of Technology, 2013)
Structural reliability analysis was carried out on the Nigerian grown Abura timber, to ascertain its structural performance as timber bridge beams. Samples of the Nigerian grown Abura timber were bought from timber market, seasoned naturally and their structural/strength properties were determined at a moisture content of 18%. The determined strength properties were subjected to statistical analysis to determine some statistical parameters used in the design. Structural analysis and deterministic design of a timber bridge beam using the Nigerian grown Abura timber in accordance with BS 5268 were carried out under the Ultimate Limit State of loading. A computer programme in FORTRAN language was developed and used for reliability analysis of the Nigerian grown Abura timber bridge beam so designed, to ascertain its level of safety using First-Order Reliability Method (FORM). Sensitivity analysis was carried out by varying the depth of beam, imposed live load, breadth of the beam, unit weight of the Abura timber, span of the beam as well as the end bearing length. The result revealed that the Nigerian grown Abura timber is a satisfactory structural material for timber bridge beams at depth of 400mm, breadth of 150mm and span of 5000mm under the ultimate limit state of loading.  The probabilities of failure of the Nigerian grown Abura timber bridge beam in bending and deflection are respectively, under the design conditions.